Evolution of the Genes Encoding Effector Candidates Within Multiple Pathotypes of Magnaporthe oryzae - Kim, Ki-Tae (Front Microbiol, 2019)
Magnaporthe oryzae infects rice, wheat, and many grass species in the Poaceae family by secreting protein effectors. Here, we analyzed the distribution, sequence variation, and genomic context of effector candidate (EFC) genes in 31 isolates that represent five pathotypes of M. oryzae, three isolates of M. grisea, a sister species of M. oryzae, and one strain each for eight species in the family Magnaporthaceae to investigate how the host range expansion of M. oryzae has likely affected the evolution of effectors. We used the EFC genes of M. oryzae strain 70-15, whose genome has served as a reference for many comparative genomics analyses, to identify their homologs in these strains. We also analyzed the previously characterized avirulence (AVR) genes and single-copy orthologous (SCO) genes in these strains, which showed that the EFC and AVR genes evolved faster than the SCO genes. The EFC and AVR repertoires among M. oryzae pathotypes varied widely probably because adaptation to individual hosts exerted different types of selection pressure. Repetitive DNA elements appeared to have caused the variation of some EFC genes. Lastly, we analyzed expression patterns of the AVR and EFC genes to test the hypothesis that such genes are preferentially expressed during host infection. This comprehensive dataset serves as a foundation for future studies on the genetic basis of the evolution and host specialization in M. oryzae.